Effect of electronic word of mouth on repurchase intention mediated by brand attitude - Heryana, Dwi Kadek; Yasa, Ni Nyoman Kerti (International research journal of management, IT and social sciences, 2020)
This research aims to consider the effect of electronic word of mouth on repurchase intention mediated by the brand in the context of purchasing local clothing brand in the City of Denpasar. The unit of analysis of the study is the costumer of local clothing brands as respondents. This study is a survey of 121 respondents, by using PLS to connect constructs electronic word of mouth, repurchase intention and brand attitude. The results showed that there are significant relationships of electronic word of mouth on repurchase intention, electronic word of mouth on brand attitude, as well as brand attitude on repurchase intention. This study also found the mediating effect of brand attitude on the relationship between electronic word of mouth and repurchase intention of the local clothing brand. The implications of these findings indicate that local clothing brand management plans in terms of the use of electronic word of mouth must be made explicit and shared among all costumer. Moreover, the management must positively gain the knowledge of digital advertising especially on the use of online reviews of a product and willingness to implement electronic advertising to achieve business goals.